(untitled) (Kriminalističke teme, 2019)
Reason(s) for writing and research problem(s): Suicide terrorism as - "Modus operandi" is undoubtedly the most common, and almost everyday, way of committing a terrorist act. The aim of this paper is to emphasize the fact and try to show that the body is a socio-cultural construct and to highlight those aspects of bodies that are fundamentally linked to terrorism as the greatest social problem of today. Methodology / Design: In this paper, the goal is to expose the perception of the mode of operandi of self-destructive terrorism through the use of several different methods of both general and special scientific methods. Analyzes of content, analytical-synthetic methods, methods of abstraction and concretization, method of observation are the most present. Research / work limitations: Is the body as the basis for a suicide terrorist act to investigate, whether suicides of terrorists have special features in their physical behavior, can this behavior be characterized and recognized? Results / Findings: Conclusions and recommendations General conclusion: Suicide terrorism has become the most common form of terrorist manifestation, every effort and attempt to identify factors that point to the possibilities of discovery. Justification of research / work: Knowing the problem of suicidal terrorism and knowing about the forms of its manifestation is the first step in its analysis. The second step in the analysis is inevitably directed towards the critical disclosure of certain mechanisms that seek to condemn the activities of this type of terrorists.